Pathogens causing root rot in soursop (Annona muricata L.), in Nayarit, Mexico - Cambero-Ayón, Carlos Bryan; Rios-Velasco, Claudio; Luna-Esquivel, Gregorio; López-Guzmán, Graciela Guadalupe; Estrada-Virgen, Mario Orlando; Cambero-Campos, Octavio Jhonathan (Ecosistemas y Recursos Agropecuarios, 2024)
In commercial soursop orchards in the state of Nayarit, Mexico, trees with apparent symptoms of root rot are observed, without the causal agent being known. Therefore, the objective of the research was to identify the fungi that cause soursop root rot. From January 2020 to January 2021, in orchards of Compostela and San Blas, Nayarit, from two trees with symptoms of possible root rot, root sections with rot were collected. Microorganisms associated with the disease were isolated and identified to carry out pathogenicity tests in one-year-old soursop trees. Fusarium falciforme and Lasiodiplodia theobromae were identified as root pathogens, both fungi are reported for the first time in this fruit tree and for Mexico.
Keywords: Isolation; disease; identification; necrosis; pathogenicity